Neophilia dan Dampaknya Bagi Kualitas Pengalaman Penikmat Makanan Lokal Kota Kebumen - Sigit Wibawanto (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2020)
This study is limited to the discussion of food consumption which is explored from the dimensions of local food preferences in destinations. This study has three objectives: to establish the neophilic tendency of foods to determine the consumption of new foods; how is the quality of food experiences with neophilia personalities; and how tourist food experiences are moderated by travel motives for new experiences about food in the places visited. This study illustrates a descriptive research scheme, tested on travelers who happen to pass through the city of Kebumen who enjoy "Ambal" satay food by 100 respondents. The study used a partial statistical test (t-test) and Moderated Regretion Analysis (MRA) to look for the effect of variable X on the Y variable. The results showed neophilia personality had a positive effect on the quality of experience. Travel motives that moderate the neophilia personality are not able to moderate the relationship of the neophilia personality to the quality of experience. The conclusions of the study show the higher the neophilia personality and travel motives, the more it can affect the quality of the experience but not with moderation.